2018
DOI: 10.1016/j.foodcont.2018.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Lethal effects and mechanism of infrared radiation on Sitophilus zeamais and Tribolium castaneum in rough rice

Abstract: The objective of this study was to investigate the characteristics of adult Sitophilus zeamais and Tribolium castaneum, and the 21.1% dry base (d.b.) MC of rough rice by ATR-FTIR spectra, and determine the theoretical optimum infrared (IR) heating temperature of the tested samples. In laboratory experiments, a ceramic IR drying device was used to heat infested rough rice to research the mortality of Sitophilus zeamais and Tribolium castaneum, the drying characteristics of rough rice, and milling quality. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 26 publications
0
13
0
1
Order By: Relevance
“…As shown in Figure 1, two surface temperature curves of rice intersect at 50 s. The surface temperature of rice treated by these two ways reached the same (60°C). The relevant study has shown that the safe storage of rice can be realized at the rice temperature of 60°C by infrared radiation treatment (Ding et al., 2015; Pei et al., 2018). MW radiation has a similar mechanism with infrared radiation.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 1, two surface temperature curves of rice intersect at 50 s. The surface temperature of rice treated by these two ways reached the same (60°C). The relevant study has shown that the safe storage of rice can be realized at the rice temperature of 60°C by infrared radiation treatment (Ding et al., 2015; Pei et al., 2018). MW radiation has a similar mechanism with infrared radiation.…”
Section: Resultsmentioning
confidence: 99%
“…The efficacy of infrared treatment in plant protection has been bolstered by other studies in connection with a wide range of arthropod pests, including those posing a threat in public health [21,22] and forestry [23], as well as by stored product pests [1,4,8]. From the genus Sitophilus primarily, the maize weevil, S. zeamais [19,24] and the rice weevil, S. oryzae have been examined in previous investigations [19].…”
Section: Discussionmentioning
confidence: 99%
“…Another way is the determination of quality change in food caused by insects [15] or in direct pest management. Numerous efforts have already been made in its practical application in connection with its utilization to combat several stored product pests, for instance, Sitotroga cerealella (Olivier, 1789) [16], Rhyzoperta dominica, Fabricius, 1792 [17], Sitophilus oryzae (L., 1763) [18], Sitophilus zeamais (Motschulsky, 1855) and Tribolium castaneum (Herbst, 1797) [19].…”
Section: Introductionmentioning
confidence: 99%
“…Electromagnetic radiations are a wide spectrum, including ionizing radiations such gamma rays, X‐rays, and nonionizing radiations such as ultraviolet, visible light, microwaves, infrared, and radiofrequency waves. Ionizing radiations are used as a tool for disinfestation, whereas the scope of nonionizing radiations are well established by researchers (Das, Kumar, & Shah, 2013; Jiao, Tang, Wang, & Koral, 2017; Pei et al., 2018; Subramanyam, Flinn, Gwirtz, Khamis, & Dogan, 2011; Vadivambal, Jayas, & White, 2007). Electromagnetic energies are generally used for fast and efficient heating of food and agriculture produces, and the applications of these thermal methods extend to drying, heating, disinfection, and pest management (Mazima, Johnson, Manasseh, & Kaijage, 2018).…”
Section: Existing Disinfestation Techniquesmentioning
confidence: 99%
“…Kirkpatrick (1975) studied IR disinfestation at a temperature of 48.6 °C in bulk wheat for S. oryzae and R. dominica and got 93% and 99% mortality, respectively. The insect bioassay experiments were performed using IR in rice (Duangkhamchan et al., 2016) and wheat (Khamis, Subramanyam, Dogan, & Gwirtz, 2011) and its effects on nutritional and milling qualities were studied (Ding et al., 2018; Pan et al., 2008; Pei et al., 2018). Khir, Venkitasamy, and Pan (2019) discussed the efficiency of IR drying in rice and the applications in food processing and preservation.…”
Section: Existing Disinfestation Techniquesmentioning
confidence: 99%